Chinese Expatriates’ Willingness Regarding Thailand-Exploring the Effects of Perceived Organizational Support, Cultural Intelligence, Overseas Study Experience and Overseas Work Experience - Chou, I-WEN; Guo, Jing; Xu, Yan (Connexion: Journal of Humanities and Social Sciences, 2023)
With the advent of globalization and multinational organizations, the number of Chinese corporate employees deployed abroad is increasing yearly. During the epidemic, the situation of expatriation is different than it was before. Based on the background of more exchanges between China and Thailand than ever before, this study aims to investigate the expatriation willingness of Chinese employees to Thailand in the post-pandemic era and to verify the relationship between cultural intelligence (motivational cultural intelligence, behavioral cultural intelligence, cognitive cultural intelligence, and Meta-cognitive cultural intelligence and expatriation willingness to Thailand. Using a network distribution form, a total of 165 valid samples were collected from full-time employees of Chinese companies (working in companies within China). The data was analyzed using SPSS 25.0 and AMOS 26.0 for reliability and regression analysis. The conclusion is that (1) Motivational CQ and Cognitive CQ have a significant positive relationship with the expatriation willingness to Thailand; (2) The expatriation willingness to Thailand is affected by demographic variables such as overseas study experience and overseas work experience; (3) Perceived Organizational Support has a positive effect on the expatriation willingness to Thailand. The results of this study can provide a reference for human resource management in dispatch in the post-pandemic era and make up for the gap in previous research.